Fono(alvo) : a nasalidade em jogo - Costa, Wirna Maria Matos Santos (2021)
This research has as general objective to analyze the phonological process of nasalization in the writing of students of the sixth year of Elementary School of a State College in the city of São Cristóvão/SE. According to Mattoso Câmara (1992), the nasalization process is the result of the encounter of a vowel with a nasal consonant. This encounter can be marked by a distinctive action, which results in a change of meaning and we call it phonological and, without distinction of meaning, we call it phonetics. This only presents changes in the phone, that is, it presents linguistic variation such as /banana/ or /bãnãna/. In “minto” and “mito” [miNto] and [mito], the change in phoneme changed the meaning of the word. In this study, we will seek to investigate the linguistic and extralinguistic contexts in relation to the erasure, insertion or exchange of the nasal archiphoneme, resulting from a possible interference of speech in writing, thus causing deviations. Interest in the topic emerged from the researcher's empirical observation regarding spelling errors made in the students' writing, which were later described as resulting from the nasalization present in their speech. The research is justified, therefore, by the necessary pedagogical intervention in students' writing, with the aim of reducing the erasure, insertion or transformation of nasality in writing. Thus, working on the phonological nasality presented in the written texts of elementary school students implies the improvement of teaching-learning of the Portuguese language. The work is methodologically based on the assumption of Action Research (THIOLLENT, 1986), making a quantitative and qualitative approach. As a theoretical contribution, we resorted to studies: by Mattoso Câmara Jr. (1986, 1992), in which the author discusses the difference between nasality and nasalization in Portuguese; by Cristófaro Silva (2003); Hour (2009); Callou and Leite (2009); Bisol (2011); Seara, Nunes and Lazzarotto-Volcão (2011), who address the phonological processes in speech; by Bortoni-Ricardo (2005), which deals with the interference of speech in writing; Roiphe (2020), who reflects on traditional classroom games; as well as Carlos Alberto Faraco (2008) regarding the standard norm. To help students reflect on the errors detected in their written productions, a Pedagogical Game entitled “Fonoalvo” was created. The aim of the on-screen research and the pedagogical game is to reduce the phenomenon of nasalization in students' writing, to collaborate with other teachers and educational managers in improving the writing of students Elementary School students, in addition to contributing to studies in the field of phonology.